Conceptualizing and integrating intercultural communicative competence in the English Language Teaching - Abidin, M. Zaenal; Faresta, Rangga Alif; Malisa, Malisa; Narayana, I Gede Perdana Putra; Fitriani, Lina Ulfa; Andika, Jeffri Dian; Waly, Muchamad Muchibbuddin (Diksi, 2024)
Numerous higher education institutions prepare students English skills for life and jobs in a globalized world in light of current developments in international education. For many universities, they entails expanding educational exchange opportunities for domestic and international students, internationalizing the curriculum and campus, and helping students achieve intercultural competency. This research explored the concept of intercultural communicative competence in the teaching of the English language. It articulated the Byram's framework. This research was a literature study with descriptive qualitative research and the latest literature review to illustrate the importance of integrating intercultural communicative competence (ICC) to the instructor in English learning and teaching. Some collection and review of references through scientific literature sources related to ICC and the integration in English language teaching keywords were addressed. As for the author's reference sources, they were determined from 2015 to 2023. The results of the study showed that the promoting and conceptualizing ICC in English classroom practice to the teacher has an important role in helping students achieve and develop learning activities that can be practiced directly by students in everyday life. Moreover, it was also mentioned that integrating the framework of the proposed concept into English Language Teaching (ELT) could help students develop their linguistic, intercultural competence, and sociocultural skills to communicating in proper English in appropriate real-life situations, and raised the teachers' awareness.